2018
DOI: 10.1002/smr.1937
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of flexibility attributes: A flexibility framework for software developing organization

Abstract: Software developing organizations strive to achieve flexibility to maintain a competitive advantage. There is no common understanding of what characterize flexibility for a software organization beyond the scope of the software product. Without a common understanding, it is difficult to evaluate the degrees of flexibility of software development approaches. The aim of this literature review is to collect attributes that characterize flexibility. The collected attributes are consolidated into a flexibility fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Workforce. In manufacturing and management, hiring highly skilled individual is important to be flexible [9]. Four of our interviewees indicated that having good technical skills, product knowledge, and development experience is important for successful Agile practice adoption.…”
Section: A Checklist To Capture Baseline Situationsmentioning
confidence: 95%
See 4 more Smart Citations
“…Workforce. In manufacturing and management, hiring highly skilled individual is important to be flexible [9]. Four of our interviewees indicated that having good technical skills, product knowledge, and development experience is important for successful Agile practice adoption.…”
Section: A Checklist To Capture Baseline Situationsmentioning
confidence: 95%
“…Constituents are the components that make up a software organization, they are: (1) workforce -human resources and their skills and knowledge, (2) management and organization structure -deals with leadership, the organization hierarchy and roles, and coordination between the constituents, (3) process -concerted activities that takes place in the organization, (4) infrastructure -technology platforms required to conceive, build, and release the product or service [8,14]. The focus on internal constituents is selected because introducing Agile practices can affect these constituents [9].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations